Encyclopedia of medieval philosophy - Lagerlund, Henrik; SpringerLink (Online service). (Dordrecht Springer Netherlands, 2011)
Research on medieval philosophy has advanced greatly in the last thirty years, but there has not been a comprehensive encyclopedia summarizing the current research available. This two-volume reference work fills that void. The Encyclopedia of Medieval Philosophy covers all areas of philosophy in the Middle Ages and part of the Renaissance, ranging from 500 to 1500 CE. It contains general entries on medieval philosophers and medieval philosophies and on the key terms and concepts in the subject area, but it also provides more in-depth details and analyses of particular theories. Furthermore, in order to gain an insight into the social and cultural context of the material, entries are included on the teaching of philosophy, the career of philosophers, and the place of philosophy within the universities. Complete with cross-references between key words and related essays to enable efficient searches, this Encyclopedia is exhaustive, unprecedented, and user-friendly. It is indispensable for scholars of medieval philosophy and of the history of ideas, and it is also useful for anyone interested in medieval ideas and thought.
Electronic reproduction.
Keywords: Philosophy, Medieval -- Encyclopedias; Electronic books